Effect of hydrogen atoms on potassium-ion electrets used in vibration-powered generators. (April 2023) - Ohata, Yoshiki; Araidai, Masaaki; Ishiguro, Takuma; Mitsuya, Hiroyuki; Toshiyoshi, Hiroshi; Shibata, Yasushi; Hashiguchi, Gen; Shiraishi, Kenji
Abstract: Potassium-ion electrets, which are mainly composed of amorphous silica and potassium atoms, can accumulate negative charges and are expected to be useful for future vibration powered generators. According to previous research, the origin of the accumulation of negative charges was revealed to be related to the presence of SiO5 structures in amorphous silica. In general, Si–O bonds are so stable that potassium-ion electrets are expected to retain a high electric potential longer than previously studied materials and are therefore being studied intensively for practical use. However, charge decay phenomena were observed in previous experiments, and this presents serious problems. In this study, we focus on the role of hydrogen which is considered to be one of the origins of charge decay and have investigated the behavior of hydrogen in potassium-ion electrets and the mechanism of the charge decay using first-principles calculations. As a result, we found that hydrogen atoms can create a positively charged characteristic local structure or break SiO5 structures and therefore cause degradation of the negative charge storing ability of potassium-ion electrets.